2020
DOI: 10.1074/jbc.ra120.012934
|View full text |Cite
|
Sign up to set email alerts
|

MtcB, a member of the MttB superfamily from the human gut acetogen Eubacterium limosum, is a cobalamin-dependent carnitine demethylase

Abstract: The trimethylamine methyltransferase MttB is the first described member of a superfamily comprising thousands of microbial proteins. Most members of the MttB superfamily are encoded by genes that lack the codon for pyrrolysine characteristic of trimethylamine methyltransferases, raising questions about the activities of these proteins. The superfamily member MtcB is found in the human intestinal isolate Eubacterium limosum ATCC 8486, an acetogen that can grow by demethylation of L-carnitine. Here, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(101 citation statements)
references
References 68 publications
6
94
1
Order By: Relevance
“…E. limosum has been previously demonstrated to demethylate several QAs (8,9,46), but not the proatherogenic QA, -butyrobetaine. We found that when E. limosum ATCC 8486 is cultured with butyrobetaine (Fig.…”
Section: E Limosum Grows While Concomitantlymentioning
confidence: 99%
“…E. limosum has been previously demonstrated to demethylate several QAs (8,9,46), but not the proatherogenic QA, -butyrobetaine. We found that when E. limosum ATCC 8486 is cultured with butyrobetaine (Fig.…”
Section: E Limosum Grows While Concomitantlymentioning
confidence: 99%
“…There are evidences implying the role of gut microbiota as a mediator of the association between diet, TMAO, and diseases, with alteration in the composition or structure of intestinal microbiota influencing TMAO production and hence, affecting the risk of colonic lesions ( Koeth et al., 2013 ; Tang et al., 2013 ; Romano et al., 2015 ; Cho et al., 2017 ; Shi et al., 2018 ; Chan et al., 2019 ). Of note, although most of the intestinal microbiota promote TMAO production from its precursors , Eubacterium limosum was shown to be able to metabolize TMA precursors through carnitine demethylation to form a product that cannot be readily converted into TMA, revealing the potential of this gut bacterium in reducing TMAO level in the gut ( Kountz et al., 2020 ).…”
Section: The Interactions Between Diet Gut Microbiota and Colorectamentioning
confidence: 99%
“…In these environments, they are not only involved in the carbon cycling via acetate but also extensively involved in the metabolism of ethanol, methanol, formate, butyrate, lactate, vanillate, chlorinated compounds, cellulose, mono-tetra saccharides, methylated amines etc. (Wolin and Miller, 1994;Das and Ljungdahl, 2003;Lovell and Leaphart, 2005;Rey et al, 2010;Hügler and Sievert, 2011;Wen et al, 2015;Lechtenfeld et al, 2018;Yang, 2018;Picking et al, 2019;Kountz et al, 2020).…”
Section: Scope Of Acetobasementioning
confidence: 99%